The Development of Learning Design of Human Reproductive System with Religious Science Insights to Improve Critical Thinking Ability of Madrasah Aliyah’s Students - Khomariyah, Siti Ayu; Alimah, Siti; Setiati, Ning (FMIPA UNNES, 2021)
MA Negeri Rembang and MA Mu'allimin Mu'allimat Rembang are religious-based schools but there has been no integration between science religions in every learning and still lack of teaching materials. There is no book that integrates religion in biological material. The purpose of this research is to produce materials to teach human reproductive system with religious science insight and to improve the critical thinking ability of MA students. The research and development design (R&D), the development model used by ADDIE using 2 classes as the research subjects: XI- science of MA Negeri Rembang and XI- science of MA Mu'allimin Mu'allimat Rembang. The instruments used were tests and non-tests, which consisted of 10 question items to measure students' critical thinking abilities, validation questionnaires, teacher and student responses questionnaires, and also interview guides. The result of the syllabus validation from the material expert gave an average score of 0,85 and the media expert gave an average score of 0,95. The validation results of lesson plan from material experts gave an average score of 0,83 and media experts gave an average score of 0,98. The results showed that the valid teaching materials were excellent categories. The material expert gave an average score of 4,25 and media experts gave an average score of 5. The average responses score from MA Negeri Rembang’s teachers was 85 and MA Mu'allimin Mu'allimat Rembang’s teachers was 79. The average score of MA Negeri Rembang students' responses to the teaching materials reached 98 and MA Mu'allimin Mu'allimat Rembang students was 97. Based on pre-test and post-test results for simple argumentation ability indicators obtained an average score of N-gain students MA Negeri Rembang 0,75 and MA Mu'allimin Mu'allimat Rembang 0,70. The indicator of ability to connect between concepts obtained an average score of N-gain in MA Negeri Rembang of 0,69 and MA Mu'allimin Mu'allimat of 0,76. The average post-test result score for the indicator of ability to connect between the concepts of MA Negeri Rembang reached 89,64 and MA Mu'allimin Mu'allimat reached 86.73, while the indicator of ability to give simple arguments MA Negeri Rembang reached 88,73 and MA Mu'allimin Mu'allimat reached 86,82. It can be concluded that teaching materials of human reproductive system religious science insight was valid and contributed to improve the ability of critical thinking students. Therefore, teaching materials can be used in the learning of the human reproductive system.